Testosterone testing in adult males - Ho, C.K. (2011)
The number of requests for testosterone testing in adult males has been increasing in recent years. In this review, the biochemistry and physiology of testosterone in males relevant to the chemical pathologist or clinical biochemist is outlined. The methodology for total testosterone and various laboratory tests associated with the assessment of testosterone status including free testosterone, calculated free testosterone (CFT), bioavailable testosterone (BAT) and free androgen index (FAI) is then summarised. Clinical and laboratory criteria for the diagnosis of late-onset hypogonadism (LOH) in men are critically discussed with particular emphasis on the interpretation of laboratory test results. Finally, other indications for testosterone testing in adult men such as infertility are also reviewed.